2022
DOI: 10.1186/s12903-022-02269-0
|View full text |Cite
|
Sign up to set email alerts
|

A prediction model for xerostomia in locoregionally advanced nasopharyngeal carcinoma patients receiving radical radiotherapy

Abstract: Background This study was to evaluate the predictors of xerostomia and Grade 3 xerostomia in locoregionally advanced nasopharyngeal carcinoma (NPC) patients receiving radical radiotherapy and establish prediction models for xerostomia and Grade 3 xerostomia based on the predictors. Methods Totally, 365 patients with locoregionally advanced NPC who underwent radical radiotherapy were randomly divided into the training set (n = 255) and the testing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Of the 42 included studies, 10 unique symptoms were reported as outcome variables in the predictions. Those included were xerostomia (9/42, 14%) [ 27 , 30 , 34 , 49 - 51 , 55 , 58 , 60 ], depression (8/42, 13%) [ 22 , 33 , 37 , 41 , 43 , 45 , 52 , 59 ], pain (8/42, 13%) [ 20 , 25 , 26 , 35 , 37 , 40 , 42 , 56 ], fatigue (6/42, 10%) [ 23 , 24 , 29 , 38 , 42 , 44 ], anxiety (3/42, 5%) [ 33 , 46 , 52 ], sleep disturbance or insomnia (3/42, 5%) [ 26 , 28 , 52 ], nausea or vomiting (3/42, 5%) [ 17 , 26 , 29 ], weight loss (2/42, 3%) [ 47 , 53 ], cognitive impairment (2/42, 3%) [ 21 , 36 ], and diarrhea (2/42, 3%) [ 29 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 42 included studies, 10 unique symptoms were reported as outcome variables in the predictions. Those included were xerostomia (9/42, 14%) [ 27 , 30 , 34 , 49 - 51 , 55 , 58 , 60 ], depression (8/42, 13%) [ 22 , 33 , 37 , 41 , 43 , 45 , 52 , 59 ], pain (8/42, 13%) [ 20 , 25 , 26 , 35 , 37 , 40 , 42 , 56 ], fatigue (6/42, 10%) [ 23 , 24 , 29 , 38 , 42 , 44 ], anxiety (3/42, 5%) [ 33 , 46 , 52 ], sleep disturbance or insomnia (3/42, 5%) [ 26 , 28 , 52 ], nausea or vomiting (3/42, 5%) [ 17 , 26 , 29 ], weight loss (2/42, 3%) [ 47 , 53 ], cognitive impairment (2/42, 3%) [ 21 , 36 ], and diarrhea (2/42, 3%) [ 29 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the predictive ability of the four candidate models suggests that alternative approaches to incorporating dose-volume histograms paired with modern machine learning approaches can provide improved discrimination for the prediction of post-radiation hyposalivation. These improvements are likely due to information loss in the way in which the LKB model and similar approaches which rely on simple low-dimensionality summaries of the DVH incorporate the DVH information, such as average organ dose [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Roesink et al [ 7 ] performed a study in 2001 in which they used a cohort of 108 patients to estimate the parameters of the LKB for parotid glands and salivary hypofunction. More recently, Beetz et al [ 8 ] and Li et al [ 9 ] developed regression models that predict salivary hypofunction using a variety of clinical and demographic information in addition to a DVH-derived mean organ dose in cohorts of size 167 and 365 respectively. Still others have attempted to predict either xerostomia or salivary hypofunction without using any data on the radiation plan [ 10 , 11 ] while others have turned to delta radiomics [ 12 ] for prediction, although these calculations cannot be performed in the radiation planning phase.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limitation of the anatomical location of NPC, the radiation field area often involves the surrounding normal tissues. The radical dose exceeds the tumor tolerance; thus, the radiotherapy-induced damage to the tissues and organs in the radiation area is extensive and lasting [ 3 ]. Parapharyngeal space is the most common site of lymph node metastasis, and the parotid gland is adjacent to the parapharyngeal space, rendering it inevitable to be exposed to high-doses radiation during radiotherapy and one of the organs at risk of radiotherapy in NPC patients.…”
Section: Introductionmentioning
confidence: 99%